Phytoremediation of Tilapia (Oreochromis Niloticus) Aquaculture Wastewater Using Spirulina sp. - Latifa Mirzatika Al-Rosyid; Musarofa Musarofa; Yuvita Dian Siswanti; Vania Zitha Amodia; Kasih Imani Putri Sugiarto (Institute of Multidisciplinary Research and Community Service, 2026)
Tilapia (Oreochromis niloticus Linnaeus, 1758) aquaculture generates nutrient-rich wastewater containing ammonia, nitrate, and phosphate that may degrade receiving water quality and promote eutrophication. Microalgae-based phytoremediation has emerged as a sustainable alternative for nutrient removal while simultaneously producing valuable biomass. This study aimed to evaluate the effectiveness of Spirulina sp. in treating tilapia aquaculture wastewater and to assess its growth performance under different wastewater concentrations. A laboratory experiment was conducted using five treatments consisting of a negative control (wastewater without Spirulina), a positive control (Spirulina cultured in 100% Zarrouk medium as the optimum growth reference), and wastewater concentrations of 25% (P1), 50% (P2), and 75% (P3). Ammonia, nitrate, and phosphate concentrations were analyzed every two days. At the same time, the relative growth of Spirulina sp. was monitored daily, and chlorophyll content was determined at the end of the cultivation period. The positive control cultivated in 100% Zarrouk medium, representing the optimum growth condition, achieved the highest relative growth of 716.9% on day 9 and the highest chlorophyll content of 0,62 mg/L. In comparison, wastewater treatments resulted in lower physiological performance but demonstrated considerable phytoremediation capacity, with maximum removal efficiencies for ammonia, nitrate, and phosphate of 48.79%, 71.87%, and 55.68%, respectively. Moderate wastewater concentrations produced superior phytoremediation performance compared with higher wastewater loading, indicating that excessive nutrient concentrations reduced nutrient assimilation efficiency. Wastewater concentrations above the optimum level also suppressed the physiological performance of Spirulina sp., as reflected by lower relative growth and chlorophyll content. These findings demonstrate that Spirulina sp. is a promising eco-friendly phytoremediation agent for tilapia aquaculture wastewater and highlight the importance of optimizing wastewater concentration to achieve both high nutrient removal efficiency and sustainable microalgal growth. Keywords: Spirulina sp., Tilapia, Phytoremediation, Aquaculture, Wastewater